(untitled) (Journal of Asian Development Studies, 2014)
The mass media have been blamed for serving elitist audiences since programmes aired and articles published are either linguistically inaccessible to rural audiences or are of little relevance to deprived communities. This study set out to investigate the effectiveness of the mass media in providing information needed to advance the development of the most deprived part of Ghana, Northern Ghana. It aims at establishing the perceptions of media editors on the contribution made by the media towards Northern Ghana’s development. It also attempts to determine the extent to which mass media stories on Northern Ghana are development-oriented. Using content analysis of selected radio and television programmes and newspaper publications as well as interviews of media editors, the study revealed that what editors applaud as their contribution to the development of Northern Ghana was simply publishing challenges of the North in their various media outlets. Analyses of media content on agriculture, education, health and the economy of Northern Ghana confirmed the fact that media stories fell short of fulfilling the tenets of development journalism. The study recommends a new approach to the practice of development journalism in order to enhance progress in deprived communities. It proposes the re-orientation of journalists to play development advocacy roles.